Counterintuitive DNA destabilization by monovalent salt at high concentrations due to overcharging - Chen Zhang; Fu-Jia Tian; Hong-Wei Zuo; Qi-Yuan Qiu; Jia-Hao Zhang; Wei Wei; Zhi-Jie Tan; Yan Zhang; Wen-Qiang Wu; Liang Dai; Xing-Hua Zhang (Nature Communications)
Abstract Monovalent salts are generally believed to stabilize DNA duplex by weakening inter-strand electrostatic repulsion. Unexpectedly, our force-induced hairpin unzipping experiments and thermal melting experiments show that LiCl, NaCl, KCl, RbCl, and CsCl at concentrations beyond ~1 M destabilize DNA, RNA, and RNA-DNA duplexes. The two types of experiments yield different changes in free energy during melting, while the results that high concentration monovalent salts destabilize duplexes are common. The effects of these monovalent ions are similar but also have noticeable differences. From 1 M to 4 M, DNA duplex is destabilized by about 0.3 k B T/bp and the melting temperature decreases by about 10 oC. Our all-atom simulations reveal this effect is caused by overcharging, where excessive ion absorption inverts the effective DNA charge from negative to positive. Furthermore, our coarse-grained simulations obtain a phase diagram that indicates whether DNA overcharging occurs at a given cation valence and concentration. These findings challenge the traditional belief that DNA overcharging occurs only with multivalent ions and have significant implications for polyelectrolyte theory, DNA nanomaterials, DNA nanotechnology, and DNA biophysics.